Digital Transformation in Halal Product Marketing: A Maqasid al-Shariah Approach - Author, Muhammad Nailul (Iqtishodia: Jurnal Ekonomi Syariah, 2025)
This study explores the digital transformation in halal product marketing through the lens of Maqasid al-Shariah, aiming to identify ethical and effective strategies aligned with Islamic values. Utilizing a qualitative approach and purposive sampling, five informants including one key informant from BAZNAS and four halal entrepreneurs from the SOHIB (Sobat Hidup Berkah) community were interviewed. The findings reveal that halal digital marketing practices uphold the five key principles of Maqasid al-Shariah: (1) Hifz al-Din is maintained through honest promotions and the avoidance of deceptive content; (2) Hifz al-Nafs is ensured by responsive customer service that fosters trust and consumer protection; (3) Hifz al-‘Aql is supported through educational content that enhances consumer awareness of halal benefits; (4) Hifz al-Nasl and (5) Hifz al-Mal are reflected in responsible, transparent pricing, ethical refund policies, and quality assurance for long-term business sustainability. This research proposes a conceptual model to guide halal entrepreneurs in developing digital marketing strategies that are both Sharia-compliant and competitive. The study contributes to the literature on Islamic marketing and offers practical insights for the halal industry in the digital era